2-Ethyl-5-triphenylmethyl-1,3-dioxane - Yuan, Lin; Shi, Jiang-Hua; Zhang, Min; Ng, Seik Weng (International Union of Crystallography, 2010)
In the title compound, C25H26O2, the dioxane ring adopts a chair conformation with the two substituent groups occupying equatorial positions.